Patch testing with hair cosmetic series in Europe: a critical review and recommendation. (15th June 2015) - Uter, Wolfgang; Bensefa‐Colas, Lynda; Frosch, Peter; Giménez‐Arnau, Ana; John, Swen M.; Lepoittevin, Jean‐Pierre; Lidén, Carola; White, Ian R.; Duus Johansen, Jeanne
Summary Many key ingredients of hair cosmetics (in particular, dyes, bleaches, and hair‐styling agents) are potent (strong to extreme) contact allergens. Some heterogeneity is apparent from published results concerning the range of allergens for which patch testing is important. The objective of the present review was to collect information on the current practice of using 'hair cosmetic series', and discuss this against the background of evidence concerning consumer/professional exposure and regulatory aspects to finally derive a recommendation for a 'European hair cosmetic series'. The methods involved (i) a survey targeting all members of the COST action 'StanDerm' (TD1206) consortium, (ii) analysis of data in the database of the European Surveillance System on Contact Allergies (ESSCA), and (iii) literature review. Information from 19 European countries was available, partly from national networks, and partly from one or several departments of dermatology or, occasionally, occupational medicine. Apart from some substances being tested only in single departments, a broad overlap regarding 'important' allergens was evident. Some of the substances are no longer permitted for use in cosmetics (Annex II of the Cosmetics Regulation). An up‐to‐date 'European hair cosmetics series', as recommended in the present article, should (i) include broadly used and/or potent contact allergens, (ii) eliminate substances of only historical concern, and (iii) be continually updated as new evidence emerges.